Interpretasi Pastoral Inklusif Dan Berkeadilan Sosial Pada Upacara Pembasuhan Kaki Di Puspas KAJ Samadi - Dewi Anggraini (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2024)
The foot-washing ceremony during the Maundy Thursday Mass at PusPas KAJ Samadi introduced a new pastoral interpretation. The ritual was performed in a different way than the traditions of the Roman Catholic Church before it. The flow of framing analysis is utilized in this article to highlight and articulate interpretations of social reality, which are expressed through speech, video framing, and text. The foot-washing conveys a pastoral message that emphasizes the importance of inclusion and social justice values. So, the foot-washing at PusPas KAJ Samadi is more than just a ritual for the Maundy Thursday Mass. But the foot-washing also brings about the actualization of Jesus' mandatum for fulfilling the needs of pastoral ministry today.